Bibliometric Analysis of Industry 4.0 in the supply chain: An exploratory approach - Anaya Tinco, Juan Alberto (2022)
Discussions about Industry 4.0 and its relationship with supply chains are a topic that has been growing over tim e. In theory, this new technological revolution can transform industries and their business models entirely as there are new ways to o ffer value to customers. Developing new technologies will allow sup p ly chains, mainly in manufacturing companies, to change their paradigms, achieving a competitive advantage over others. This article's main objective is to investigate the current state of Industry 4.0 in supply chains, exploring the technologies that enable it, the existing uses in the processes, its benefits, and its challenges. For this purpose, a systematic literature review was conducted, in addition to bibliometric analysis.